The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1375/bech.21.4.269.66105
|View full text |Cite
|
Sign up to set email alerts
|

Training in Emotion Regulation as a Treatment for Binge Eating: A Preliminary Study

Abstract: Binge eating within Binge Eating Disorder (BED) may represent ineffective management of, and inappropriate escape from, strong, dysphoric emotions, but treatments have been slow to incorporate an emotion regulation focus. Eleven women meeting criteria for BED participated in 11 sessions (2 hours per week) of a psychoeducational group program providing training in emotion recognition and management, problem-solving, assertion training, relaxation and stress management. Outcome was evaluated using a multiple-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 47 publications
(49 reference statements)
0
38
0
2
Order By: Relevance
“…Depression is also related to anger-focused rumination (Gilbert, Cheung, Irons, & McEwan, 2005), and to the fear of anger (Brody, Haaga, Kirk, & Soloman, 1999). Assertiveness training is also effective in decreasing depression and binge eating episodes in women with binge eating disorder (Clyne & Blampied, 2004). These findings suggest that anger inexpressiveness may act as a vulnerability factor for depressive symptomatology.…”
Section: Discussionmentioning
confidence: 70%
“…Depression is also related to anger-focused rumination (Gilbert, Cheung, Irons, & McEwan, 2005), and to the fear of anger (Brody, Haaga, Kirk, & Soloman, 1999). Assertiveness training is also effective in decreasing depression and binge eating episodes in women with binge eating disorder (Clyne & Blampied, 2004). These findings suggest that anger inexpressiveness may act as a vulnerability factor for depressive symptomatology.…”
Section: Discussionmentioning
confidence: 70%
“…These questions are of obvious value not only from a clinical perspective but also from a theoretical viewpoint because one can demonstrate that a risk factor such as alexithymia actually contributes to health problems only by reducing or removing it and seeing whether health improves. Some studies have shown that alexithymia decreases over time during treatment of eating disorders (Becker-Stoll & Gerlinghoff, 2004;Clyne & Blampied, 2004;de Groot, Rodin, & Olmsted, 1995), yet these interventions were not attempting to reduce alexithymia directly, and the decrease in alexithymia may have been a reflection of reduced symptoms. Furthermore, these studies did not have control or comparison conditions to assess changes in alexithymia in the absence of treatment or given a different treatment.…”
Section: Can Alexithymia Be Reduced?mentioning
confidence: 99%
“…The specific impact of incorporating emotion regulation components into therapy for children and adolescents is therefore largely unexplored at this time. A few studies, however, have examined changes in emotion regulation skills following emotion regulation therapy for adults (e.g., Clyne and Blampied 2004;Mennin 2004). In the Clyne and Blampied (2004) study with bulimic women, for example, the recognition of emotion and bodily sensations improved significantly following treatment.…”
Section: The Missing Componentmentioning
confidence: 99%